Total Communication-Based Al-Qur'an Reading Instruction for Deaf Children at Qothrunnada Islamic Special School - Tri Purwanti; Imas Diana Aprilia; Budi Susetyo (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This study aims to determine how the comtal (communication total) method is applied in Al-Qur'an reading and to assess its impact on Al-Qur'an reading among deaf students at SLB Islam Qothrunnada. This study is qualitative, using descriptive and phenomenological approaches to examine the application of the Comtal method and its impact on deaf students' ability to read the Qur'an at SLB Islam Qothrunnada. The study population consisted of teachers and deaf students at SLB Islam Qothrunnada, and participants were selected through purposive sampling based on their direct involvement in implementing the Comtal method. To obtain information about the application of the Komtale method and its impact on the ability to read the Qur'an among deaf children. The subjects in this study are the principal, Islamic education teachers, and deaf students at SLB Islam Qothrunnada. The data collection techniques were observation, interviews, and documentation. The data analysis techniques were data reduction, data presentation, and conclusion. The results showed that the Comtal method, when applied to teaching deaf students at SLB Islam Qothrunnada to read the Qur'an, followed three steps: speech articulation training, reading practice, and speech teaching. The impact of applying the Comtal method in teaching deaf students at SLB Islam Qothrunnada to read the Qur'an was that they were able to read it correctly and fluently, with sign language support.